VIRTUAL COLOR 3D-MODELING IN LIVER SURGERY - D. N. Panchenkov; Yu. V. Ivanov; A. V. Kolsanov; S. S. Chaplygin; P. M. Zelter; K. A. Tupikin; D. A. Astahov; A I. Zlobin (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE of this work was to study the possibility of preoperative color 3D-modeling and intraoperative navigation through the use of the system «Avtoplan» in the surgical treatment of patients with pathology of the liver.MATERIAL AND METHODS. System «Avtoplan» was used in 32 patients with different surgical diseases of the liver: hemangioma, hydatid cyst, alveococcosis and metastatic colorectal cancer to assess the feasibility of the operation – resection of the liver of a particular volume.RESULTS. The performed 3D-modeling of the liver in the preoperative stage were used in 3 cases (10.3%) of 32 to abandon the planned surgical treatment in favor of conservative therapy due to local spread of the pathological process (in 2 cases – metastatic bilobate and in 1 case – alveococcosis organ damage). Of the 29 operated patients, in 6 (20.7%) at the stage of preoperative modeling, the planned volume of liver resection was changed: in 4 patients, in the direction of its increase in connection with the identified topographic and anatomic location of tumors, and in 2 patients, in the direction of its reduction due to the peculiarities of the blood supply to the zone of surgical interest.CONCLUSION. Preoperative 3D-modeling allowed the surgeon to better prepare for surgical intervention according to individual anatomical characteristics of the patient and to choose the optimal extent of surgery. Knowledge of 3D topography of liver lesions allowed reducing intraoperative blood loss and the likelihood of damage to intrahepatic structures (vessels, bile ducts). Postoperative 3D modeling allowed to assess the adequacy of the volume of surgery performed and could serve as an objective criterion in assessing the quality of medical care.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.